Optimization of polyphenols process and their hypoglycemic and antioxidant activities of Porphyra haitanensis - CHEN Xiao-chen; DU Xi-ping; ZHOU Li-juan; WU Ling; LI Zhi-peng; YANG Yuan-fan (Shipin yu jixie)
Objective: This study aimed to optimize the extraction process of Porphyra haitanensis polyphenols to develop natural hypoglycemic foods. Methods: The Box-Behnken response surface method was used to optimize the extraction process of P. haitanensis polyphenols. The α-glucosidase inhibition activity was applied to evaluate the hypoglycemic activity of P. haitanensis polyphenols at different harvest periods, and the antioxidant activities of them were evaluated based on DPPH, ABTS+ radical scavenging rate and ORAC value. Results: The optimal extraction process conditions were liquid-solid ratio (Vethanol∶mP. haitanensis) 51∶1, ethanol concentration 56% and ultrasonication time 51 min. Under the control of these conditions, the extracted content of polyphenols was 5.027 mg/g. The inhibition of α-glucosidase activity by P. haitanensis polyphenols was in a concentration-dependent manner, and the inhibition by the fourth-harvest-period polyphenols was significantly higher than other harvest periods polyphenols. P. haitanensis polyphenols at different harvest periods showed antioxidant activity, and the antioxidant activity of the fourth-harvest-period polyphenols was strongest. Conclusion: The high polyphenol contents, strong inhibition of α-glucosidase activity and strong antioxidant capacity of the fourth-harvest-period makes it an excellent food source for developing natural hypoglycemic foods and antioxidants.